An Exploration of Chinese Synonym Learning Methods for Indonesian Students - Mardasari, Octi Rjeky (Universitas Negeri Malang, 2024)
It is well known that the richness of Chinese vocabulary is unrivaled, including Chinese synonyms. The highly developed performance of the Chinese language can be seen in the synonyms of the Chinese language. Learning Chinese synonyms is simple but complex, and requires us to understand the nuances between them and be good at recognizing them so that we can use them accurately. Through the experience of learning and teaching, this paper finds that Indonesian students often encounter difficulties with Chinese synonyms. In addition, through the short time of this paper's internship, this paper also finds that in Indonesian classroom teaching, teachers' explanation of synonyms is not clear and to the point. This time, this paper tries to suggest some pedagogical methods for Chinese teachers to teach synonyms. This article is just a guideline, and we hope that this article can be a reference for the Chinese language teaching community.